Self-assessment and self-overcoming in Graduate Studies: foundations for an ethical and transformative practice (Práxis Educativa, 2025)
How can self-assessment processes in graduate education be developed to overcome classificatory logic and become critical, participatory, and emancipatory practices? This article discusses institutional self-assessment in Brazilian graduate programs in light of CAPES Ordinance No. 149/2018, which establishes it as a mandatory component of evaluation processes, and proposes a perspective grounded in ethical-political and formative principles. The aim is to question the limits of bureaucratic evaluation and advocate for self-assessment as a transformative pedagogical practice, inspired by Freirean pedagogy and philosophical elements of Friedrich Nietzsche, as interpreted by Mendonça. The research adopts a qualitative, theoretical-reflective approach, based on document analysis and the authors’ participation in collective self-assessment initiatives within graduate programs. The findings indicate that, although the regulation represents progress, the effectiveness of self-assessment depends on its reframing as a dialogical, critical, and context-sensitive process. It concludes that an ethical and transformative self-assessment requires active listening, democratic participation, and a commitment to institutional self-overcoming, paving the way for the reinvention of evaluation within the context of Brazilian graduate education.Keywords: Institutional self-assessment. Ethics in graduate education. Emancipatory practice.